Utilization of a cost effective lapindo mud catalyst for transesterification of waste oils - Nor Badariah Talib, 1987-; Sugeng Triwahyono; Aishah Abd. Jalil, supervisor; Che Rozid Mamat, supervisor; Fakulti Sains (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Thesis (Sarjana Sains (Kimia)) - Universiti Teknologi Malaysia, 2016